Assessment of theory of mind in Tunisian verbal children with autism spectrum disorder - Jelili, Selima; Halayem, Soumeyya; Rajhi, Olfa; Abbes, Zeineb; Mansour, Hajer Ben; Ouanes, Sami; Taamallah, Amal; Ennaifer, Selima; Ben Yahia, Houda; Ghazzei, Melek; Nabli, Ahmed; Hajri, Malek; et al. (Frontiers in Psychiatry, 2022)
The present study examined performance in Theory of Mind (ToM) in a group of 31 Arabic-speaking verbal children (7–12 years-old) with autism spectrum disorder (ASD), in comparison with neurotypical controls (NT) matched for age and for cognitive abilities. An innovative task in a digital format named “The Tunisian Social Situations Instrument” (TSSI) was used and allowed us to study four different subdomains of ToM: attribution of intention and epistemic ToM (cognitive ToM), affective ToM, and detection of faux pas (advanced ToM). Our study showed impairments in ToM in children with ASD, similar to those reported in the literature. Our findings additionally suggested that affective and advanced ToM, specifically the detection of faux pas, might be more challenging for ASD children than other components of ToM. Future studies with larger number of children may lead us to specify which subdomains are the most impaired in order to develop specific tools targeting these specific impairments.